Związki między aktywnością gospodarczą a koniunkturą giełdową w Polsce w świetle testów przyczynowości Grangera - Acedański, Jan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper investigates the relationships between stock returns and real business activity in Poland. Production index and diffusion indexes build upon data from the monthly survey on business conditions in companies are used as proxies for real activity. First, the basic evidences are presented and further inquiries are conducted using Granger-causality methodology. Although the long-run relationships are weak, an assymetry in stock prices fluctuations before and during recession and expansion periods can be noticed. The results suggest that stock returns Granger-cause real activity measured by diffusion indexes. The contemporaneous causality can also be found. When the production index is used observed relationships are multidirectional. The lack of empirical evidence for the causality relation from stock prices to investment does not support the ^-channel and the balance-sheet channel hypothesis. This result can be explained by relatively small equity markets in Poland. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 13-25